2006
DOI: 10.4028/www.scientific.net/msf.519-521.239
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intermediate Storage Temperature and Time on the Age Hardening Response of Al-Mg-Si Alloys

Abstract: Specimens of three Al-Mg-Si alloys, 6060, 6005 and 6082, were solution heat treated, stored at different temperatures for different time, and artificially aged. Properties were measured before and after artificial ageing. The natural ageing response of the alloys is dependent on the storage temperature. Decreasing storage temperature leads to a delayed onset of natural ageing, but also to a higher strength after prolonged ageing, particularly for lean alloys such as 6060. The temperature and time of intermedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 6 publications
(6 reference statements)
2
17
0
Order By: Relevance
“…For instance, in alloy 6082 artificially aged immediately after a solution treatment, the number density of β″ precipitates has been reported to be almost five times higher than that of samples naturally aged for a week followed by the same artificial ageing [12]. This has an adverse effect on the tensile properties of the alloy [1,15]. The opposite, however, is believed to occur in the 6000 series alloys with low alloying element addition [1,13,15].…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…For instance, in alloy 6082 artificially aged immediately after a solution treatment, the number density of β″ precipitates has been reported to be almost five times higher than that of samples naturally aged for a week followed by the same artificial ageing [12]. This has an adverse effect on the tensile properties of the alloy [1,15]. The opposite, however, is believed to occur in the 6000 series alloys with low alloying element addition [1,13,15].…”
Section: Introductionmentioning
confidence: 88%
“…This has an adverse effect on the tensile properties of the alloy [1,15]. The opposite, however, is believed to occur in the 6000 series alloys with low alloying element addition [1,13,15]. Chang and co-workers [13] described a "positive effect" of natural pre-ageing on precipitation hardening in an Al-0.44at%Mg-0.38at%Si alloy, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another report [22] showed that slow cooling leads to less precipitate number densities because of loss of quenchedin vacancies. Although natural aging (room temperature storage before the isothermal heat treatment) time generally influences the type of atomic clusters and consequently mechanical properties after precipitation [23,24], the slow cooling leads to lower influences on the effects of natural aging [22]. Investigations of effects of quench rates are important since a fast quenching is not always possible in industrial processes because of e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This effect is well known for wrought 6082 alloys [8]. Alloy 6004 shows the opposite behaviour, with the maximum hardness being higher when natural aging occurs before artificial aging [8]. The clusters that formed during natural aging in alloy 6082 are known to be relatively stable at typical artificial aging temperature [1], as can be seen by the small initial decrease in hardness during artificial aging of the naturally aged 6082 sample compared to the naturally aged A356 sample in Fig.…”
Section: Resultsmentioning
confidence: 84%